Ball valving laryngeal masses: a difficult “ball” in the anaesthetists’ court - Verma, Ankur; Biswas, Shubhashish; Singh, Pooja; Tyagi, Tarun; Khatri, Pankaj; Gupta, Tushar; Dabas, Surender Kumar (International Journal of Research in Medical Sciences, 2023)
Dynamic airway obstruction (also called ball-valve effect) is a serious condition often seen in glottic lesions. This is an anesthetic challenge as total airway obstruction can occur after the induction of general anesthesia. We present a case of a middle aged female who had a large laryngeal mass which was showing ball-valve effect. The patient had refused for tracheostomy despite it being the safest procedure in the circumstances. We then performed videolaryngoscopy and managed to intubate the patient with the help of some improvisation. The patient underwent a succesful and uneventful surgery.